Isoprinosine along with Favipiravir or Oseltamivir in Patients with Moderate Covid-19 at RSD Dr. Soebandi Jember - Chrysnanda Maryska; Didik Hasmono; Sofiati Diah Baisuni; Ayunda Nur Hidayatiningsih; Arina Dery Puspitasari; Retna Dwi Puspitarini; Budi Suprapti (Universitas Airlangga, 2022)
Background: Isoprinosine is an immunomodulator that is now being used to treat Covid-19 patients. Objectives: To evaluate Isoprinosine with Favipiravir or Oseltamivir in moderate Covid-19. Methods: In a retrospective observational analysis, in-hospital moderate Covid-19 patients treated between June 2020 and June 2021 were included. Results: Inclusion criteria for 364 patients were met, with 135 receiving Favipiravir-Isoprinosine (Group 1) and 229 receiving Oseltamivir-Isoprinosine (Group 2). In group 1, the majority of patients (58.50%) were female (35.60%), had no comorbidities (71.60%), were discharged with a positive PCR (74.80%), did not require a breathing apparatus (99.26%), had leukocyte levels between 4,5-11,0 (82.22%), lymphocyte levels between 25-33 (34.07%), and were discharged with no ground-glass opacity (34.07%) (54.10%), LOS was 9-13 days (50.37%), while the mortality rate was 0.70%. In group 2, the majority of patients were male (54.10%), with the highest age range being 42-56 years (35.80%), without comorbidities (69.0%), discharged with a positive PCR (72.50 %), and without the need for a breathing apparatus (99.13%), with leukocyte levels ranging from 4.5 – 11.0 (81.22 %), with lymphocyte levels ranging from 25.0 – 33.0 (26.20 %), and were discharged with no ground-glass opacity (49.34 %), LOS was 9 - 13 days (34.06 %), and the mortality rate was 0.87%.Conclusion: In this trial, it was determined that combining isoprinosine with antivirals favipiravir or Oseltamivir could produce significant clinical improvement.